Scientific Basis of the Concept of Strategic Marketing for the Development of Physical Training and Sports in Uzbekistan - Bakhriddin Juraevich, Makhmudov; Komil Shamsievich, Ziyadullaev; Akhtam Husanovich, Ibragimov; Jalalitdin Paygamovich, Narziev; Nuriddin Narimanovich, Narimanov (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the formation and scientific substantiation of the strategic marketing concept of the development of physical culture and sports. At the same time, the main directions of advertising activities of sports organizations are listed.